Extraction of Phytosterol Concentration in Different Legume Pods by Using Microwave-Assisted Hydrodistillation - Noormazlinah Noormazlinah; Norlaili Hashim; Abdurahman Hamid Nour; Mimi Sakinah Abdul Munaim; Maria Pilar Almajano; Nurul Bahirah (Universitas Gadjah Mada, 2019)
The traditional ways in the extraction of bioactive compounds using conventional methods are disadvantageous from both economic and environmental perspectives. In this, the potential of microwave-assisted hydrodistillation conditions for extraction of phytosterol from legume pods was investigated. Salkowski test performed on the legume pod has shown the reddish brown in all sample which confirmed the presence of phytosterol qualitatively. Liebermann-Burchard procedure and ultraviolet-visible spectroscopy (UV-Vis) apparatus were used to study the concentration of phytosterol at different extraction parameters which are temperature (25–80 °C), solvent concentration (50–100% v/v), irradiation time (1–10 min) and microwave power (400–800 W). The optimal conditions for highest yield of extract (0.219 mg/L) were obtained at a microwave power of 600 W, the irradiation time of 6 min, and ethanol concentration of 75% v/v. Results obtained in this study have shown the capability of microwave-assisted hydrodistillation in the extraction of phytosterol from legume pod. Further works are nevertheless required to provide a deeper understanding of the mechanisms involved to facilitate the development of an optimum system applicable to the industry.